User needs over time: The market and technology maturity model (MTMM) - Jan Silberer; Stefanie Astfalk; Patrick Planing; Patrick Müller (Journal of Innovation and Entrepreneurship, 2023)
This paper conceptualizes how consumers perceive innovations at different stages of technology maturity. The market and technology maturity model (MTMM) combines the constructs of acceptability, acceptance, and adoption with the widely used technology readiness level (TRL). The MTMM proposes that different aspects impact users' attitudes and behavior at different stages of technology maturity. To demonstrate the effect of technology maturity on the acceptance factors, a review was conducted based on previous studies on the acceptance of new technologies at various stages of technological maturity. The findings demonstrate that performance expectancy remains stable across the TRL stages, but effort expectancy tends to gain importance only after TRL 7. This indicates that consumers do not consider effort when the technology is still in early development. The results show that the importance of technology acceptance constructs differs across the stages of technology maturity. A limitation of this study is that only the most commonly used factors influencing acceptance have been considered. Future meta-studies should confirm the hypothesis with other factors such as social influence and hedonic motivation.
Keywords: 650; Technology; Adoption; Acceptability; Acceptance